The Influence of The Quality of Interpersonal Relationships on Student Self-Concept - Dinda Almira Sahputri; Najwa Aurelia; Ajeng Dwi Larasati (International Conference on Psychology and Education (ICPE), 2023)
Interpersonal relationships are an important factor in the formation of one's self-concept. This research is a type of qualitative research with a literature review approach. The keywords used are "interpersonal relationships", "self-concept", and “adolescent”. The results of this research show that the quality of interpersonal relationships influences individual self-concept. The more quality the interpersonal relationship has, the more positive self-concept the individual has. And conversely, failure in terms of interpersonal relationships will have a negative impact on one's self-concept. The quality of interpersonal relationships, along with individuals' awareness of themselves and their environment, plays a significant role in shaping both positive and negative self-concepts. This influence is evident not only in general circumstances but also within the specific context of college students.